2011
DOI: 10.1121/1.3619789
|View full text |Cite
|
Sign up to set email alerts
|

Sound, infrasound, and sonic boom absorption by atmospheric clouds

Abstract: This study quantifies the influence of atmospheric clouds on propagation of sound and infrasound, based on an existing model [Gubaidulin and Nigmatulin, Int. J. Multiphase Flow 26, 207-228 (2000)]. Clouds are considered as a dilute and polydisperse suspension of liquid water droplets within a mixture of dry air and water vapor, both considered as perfect gases. The model is limited to low and medium altitude clouds, with a small ice content. Four physical mechanisms are taken into account: viscoinertial effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
8
0
2
Order By: Relevance
“…The increased spectrum decay with distance trend can be partly explained by sound absorption. At the considered frequencies (0.5 to 180 Hz), classical atmospheric absorption due to molecular relaxation of diatomic nitrogen and oxygen is negligible, but enhanced absorption by cloud droplets has been described theoretically (Baudoin et al, , their Figure 8) with absorption coefficients of the order of 1–2 dB/km in the range 10 to 100 Hz for cumulonimbus. This would explain at least partly the loss of high frequencies with distance observed in Figure .…”
Section: Discussionmentioning
confidence: 95%
“…The increased spectrum decay with distance trend can be partly explained by sound absorption. At the considered frequencies (0.5 to 180 Hz), classical atmospheric absorption due to molecular relaxation of diatomic nitrogen and oxygen is negligible, but enhanced absorption by cloud droplets has been described theoretically (Baudoin et al, , their Figure 8) with absorption coefficients of the order of 1–2 dB/km in the range 10 to 100 Hz for cumulonimbus. This would explain at least partly the loss of high frequencies with distance observed in Figure .…”
Section: Discussionmentioning
confidence: 95%
“…In fact, real suspensions may be better described by particle size distributions. Nevertheless, there are few studies [10][11][12] which analyze the poly-disperse effect on sound propagation. For example, Gubadullin et al 10 showed that the assumption of mono-dispersion misjudges the absorption coefficients above the peak value near the particle resonance, Leroy et al 11 extended Foldy 13 and Henyey 14 models for poly-disperse bubble suspensions and verified it experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Baudoin et al [22] suggest that the assumption of monodispersion tends to overestimate the . absorption coefficient above the peak value (as observed in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Gubaidullin and Nigmatulin [24] and Bl~.udoin et al [22] investigated polydispersion effects on sound propagation, and show that it is important to take into account polydispersion. The results of Baudoin et al [22] suggest that the assumption of monodispersion tends to overestimate the .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation